Parenting Styles as Predictors of Cognitive Emotion Regulation Among High School Students - Razavi , Sepideh; Khajehpour, Leila; Moltafet , Ghavam (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the relationship between different dimensions of parenting styles and cognitive emotion regulation among high school students in Tabriz, Iran. Methods and Materials: A cross-sectional design was employed, with a sample size of 416 high school students determined using the Cochran formula. Participants were selected through multistage cluster random sampling. Data were collected using the Cognitive Emotion Regulation Questionnaire (CERQ) and the Family as a Social Context (FSC) Questionnaire. Pearson correlation was used to examine relationships between cognitive emotion regulation and each parenting dimension. Additionally, linear regression analyses were conducted to determine the predictive power of parenting styles on emotion regulation. SPSS-27 software was used for statistical analyses. Findings: Descriptive statistics indicated that warmth had the highest mean score among parenting dimensions, while rejection had the lowest. Significant correlations were found between cognitive emotion regulation and all six subscales of parenting styles. Warmth (r = 0.45), structure (r = 0.38), and autonomy support (r = 0.41) were positively correlated with cognitive emotion regulation, whereas rejection (r = -0.32), chaos (r = -0.29), and coercion (r = -0.27) showed negative correlations. Regression analyses confirmed that these dimensions significantly predicted cognitive emotion regulation, explaining 46% of the variance. Conclusion: The study highlights the crucial role of parenting styles in shaping cognitive emotion regulation among adolescents. Positive dimensions such as warmth, structure, and autonomy support enhance emotion regulation, while negative dimensions like rejection, chaos, and coercion hinder it.